Genetic polymorphism in the tumour necrosis factor alpha gene (G‐308A) is associated with persistent apical periodontitis in Brazilians - Castro, Guilherme Assed Piedade; Petean, Igor Bassi Ferreira; Paula‐Silva, Francisco Wanderley Garcia; Kuchler, Erika Calvano; Antunes, Leonardo dos Santos; Segato, Raquel Assed Bezerra; Silva, Lea Assed Bezerra; Silva‐Sousa, Alice Corrêa; Sousa‐Neto, Manoel Damião (International endodontic journal, 2023)
Aim To investigate if there was an association between genetic polymorphisms in tumour necrosis factor (TNF)‐⍺ and its receptors TNFRSF1A and TNFRSF1B with persistent apical periodontitis (PAP) in Brazilian subjects. Methodology Patients who had pulpal necrosis and apical periodontitis at the time of treatment, with at least 1‐year of follow‐up after non‐surgical root canal treatment were recalled. Three hundred and seventy eight subjects were included, 150 subjects with signs/symptoms of PAP and 228 subjects with root canal‐treated teeth exhibiting healthy perirradicular tissues (healed). Genomic DNA was extracted from saliva and used for TNF‐⍺ (rs1800629), TNFRSF1A (rs1800693) and TNFRSF1B (rs1061622) genotyping by real‐time PCR. Genotypes and alleles frequencies were evaluated by c2 or Fisher's exact tests and odds ratios were implemented (α = 5%). Results The genetic polymorphism in TNF‐α (rs1800629) was associated as a protective factor for the development of PAP (p < .05), once subjects who presented at least one allele A (AA+AG X GG), had a higher chance to lesion repair (p < .05). The polymorphisms rs1800693 and rs1061622 in TNF receptors (TNFRSF1A and TNFRSF1B, respectively) were not associated with the development of PAP (p > .05). Conclusions The observed results demonstrate that polymorphism in TNF‐α but not in its receptors is associated with PAP.